Public survey data of the research study “Ready for change? Sustainable management of common natural resources”: Thematic survey of May 2020 - University of Latvia, Advanced Social and Political Research Institute (ASPRI) of the Faculty of Social Sciences (My University, 2023)
The data set (see the description of the data set below) and its accompanying information include sociological survey conducted in May 2020 titled "GNP Resident Survey on the Perception of Organic and Conventional Farming" as part of the Fundamental and Applied Research project "Ready for change? “Sustainable management of common natural resources” (lzp-2019/1-0319). Ongoing environmental collapse is putting increasing pressure on ecosystems and social communities, particularly, in the regions of Latvia. Thus, survey of Gauja National Park residents has been conducted as part of case study to assess attitudes, understanding, and practices of organic and conventional farming, the use of natural resources and sustainable consumption. The survey achieved a sample size of 206 respondents - residents of GNP aged 18 and older. The anonymized dataset was obtained by conducting an internet survey (CAWI) within the RAIT Custom Research Baltic internet survey panel. Data collection took place from May 8, 2020, to May 14, 2020. The survey was conducted by the research center RAIT Custom Research Baltic, commissioned by researchers from the University of Latvia within the framework of the Fundamental and Applied Research project "Ready for change? “Sustainable management of common natural resources” (lzp-2019/1-0319), conducted at the Advanced Social and Political Research Institute (ASPRI) of the Faculty of Social Sciences of the University of Latvia (LU). The research was funded by the Latvian Council of Science. Description of the data sets: 1. Survey Data File (File Name: RfC_Dati_2020m_GNP.csv, also available in .sav format). 2. Variable and Value Labels for Data File (File Name: RfC_MainigoInfo_2020m.xlsx) The datasets include 62 variables, of which: 1. 59 variables are related to survey questionnaire questions and responses, including combinations of socio-demographic variables. (Survey questionnaire in the document: RfC_Aptaujas_anketa_2020m.docx); 2. Additionally, there are 3 variables - ID variable (ID), time taken to complete the survey questionnaire (Time) and the combined variable for place of residence (gnpiedz) – living in inhabited areas of GNP territories (response code 1) and living in Cēsis, Sigulda (response code 2), which is a consolidated question D1 in the survey questionnaire. Question D1 is accessible but not deposited to adhere to anonymization principles.
Sociological survey "GNP Resident Survey on the Perception of Organic and Conventional Farming"
Keywords: environmental attitude; environmental behaviour; pro-environmental behaviour; use of natural resources; sustainable consumption; organic farming; Research Subject Categories::SOCIAL SCIENCES::Social sciences